Genetic and physiological alterations occurring in a yeast population continuously propagated at increasing temperatures with cell recycling - Souza, Crisla S.; Thomaz, Daniel; Cides, Elaine R.; Oliveira, Karen F.; Tognolli, Joao O.; Laluce, Cecília [UNESP] (Springer, 2007)
This work investigated the effects of increasing temperature from 30 degrees C to 47 degrees C on the physiological and genetic characteristics of Saccharomyces cerevisiae strain 63M after continuous fermentation with cell recycling in a system of five reactors in series. Steady state was attained at 30 degrees C, and then the temperature of the system was raised so it ranged from 35 degrees C in the last reactor to 43 degrees C in the first reactor or feeding reactor with a 2 degrees C difference between reactors. After 15 days at steady state, the temperature was raised from 37 degrees C to 45 degrees C for 25 days at steady state, then from 39 degrees C to 47 degrees C for 20 days at steady state. Starter strain 63M was a hybrid strain constructed to have a MAT a/alpha, LYS/lys, URA/ura genotype. This hybrid yeast showed vigorous growth on plates at 40 degrees C, weak growth at 41 degrees C, positive assimilation of melibiose, positive fermentation of galactose, raffinose and sucrose. of 156 isolates obtained from this system at the end of the fermentation process, only 17.3% showed the same characteristics as starter strain 63M. Alterations in mating type reaction and in utilization of raffinose, melibiose, and sucrose were identified. Only 1.9% of the isolates lost the ability to grow at 40 degrees C. Isolates showing requirements for lysine and uracil were also obtained. In addition, cell survival was observed at 39-47 degrees C, but no isolates showing growth above 41 degrees C were obtained.
Keywords: Saccharomyces cerevisiae; thermal stress; genetic instability; physiological adaptation; gene segregation